2000
DOI: 10.1017/s0022377800008618
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nonlinear magnetosonic waves propagating obliquely to an external magnetic field in a collisionless plasma

Abstract: It is shown that the asymptotic evolution of finite-amplitude magnetosonic waves propagating obliquely to an external uniform magnetic field in a warm homogeneous plasma is governed by a Kadomtsev–Petviashvili equation having an extra dispersive term. The dispersion is provided by finite-Larmor-radius (FLR) effects in the momentum equation and by the Hall-current and electron-pressure corrections in the generalized Ohm's law. A double-layer-type solution of the equation is obtained, and the equation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Using Equations ( 20) and ( 21) in Equations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and collecting the lowest order terms of , we obtain the following set of equations,…”
Section: Derivation Of the Dkdv Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Equations ( 20) and ( 21) in Equations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and collecting the lowest order terms of , we obtain the following set of equations,…”
Section: Derivation Of the Dkdv Equationmentioning
confidence: 99%
“…[8] The dispersion caused by Finite-Larmor-Radius effects was studied on magnetosonic waves propagating obliquely in external magnetic field. [9] It was shown that nonlinear magnetosonic waves propagating obliquely to an external uniform magnetic field in a collisionless plasma is governed by a Kadomtsev-Petviashvili equation with an extra dispersive term.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many authors have focused their attention on investigating the formation and propagation of different modes involving magnetosonic excitations in plasmas, e.g. the KdV/KP (Kadomtsev–Petviashvili) solitons, envelope solitons, double layer shocks, etc., (Chakraborty & Das 2000; Mushtaq & Shah 2005 b ; Hussain & Mahmood 2011; Wang, Lu & Eliasson 2013). Mushtaq & Viladimirov (2010) has examined the spin effects associated with degenerate plasma species on fast and slow magnetosonic waves in a spin quantum plasma within the framework of a one-fluid quantum magnetohydrodynamic (QMHD) model.…”
Section: Introductionmentioning
confidence: 99%
“…y + · · · The dispersion and the nonlinearities then act on the slow time τ = 3/2 t. The reductive perturbative expansion is straightforward and, in the absence of Landau damping, leads to the usual Korteweg-de Vries equation (Kakutani et al, 1968;Kever and Morikawa, 1969;Chakraborty and Das, 2000). In the regimes where the strength of the Landau damping is small enough to be comparable with dispersion and nonlinearity, for example in the case of hot electrons and cold ions, a Korteweg-de Vries equation with Landau damping is obtained (Janaki et al, 1992).…”
Section: Oblique Magnetosonic Wavesmentioning
confidence: 99%
“…(40)- (44). This approximation obtained in a local frame where the z-axis points along the local magnetic field is often oversimplified by using the same formula in a fixed frame with the z-axis along the ambient field (Khanna and Rajaram, 1982;Chakraborty and Das, 2000). These two references also involve a sign error in the definition of the components xy .…”
Section: B: Second Order Flr Corrections To the Pressure Tensormentioning
confidence: 99%